2018
DOI: 10.1002/admi.201800084
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Epitaxial Growth of C60 Overlayers on Single Crystal Pentacene

Abstract: due to charge carrier delocalization. [10][11][12][13][14] Accordingly, accurate control of the crystal quality of molecular heterojunctions is desired for advancing further development of next-generation organic electronic devices. [15][16][17] In the present work, the evolution of the crystallinity of a well-ordered bimolecular heterojunction, C 60 on a single crystal surface of pentacene (C 22 H 14 ), is studied depending on the growth temperature by means of surface X-ray diffraction techniques and noncont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…On the other hand, structural analyses have disclosed well-defined assembly of several organic semiconductor molecules via heteroepitaxial growth on molecular single crystal substrates. [243][244][245][246][247][248][249][250] For instance, it was demonstrated by means of surface X-ray diffraction works that n-type semiconductor molecules of C 60 245 and perfluoropentacene (PFP; C 22 F 14 ) 250 form uniquely oriented crystallites on the single crystal surface of pentacene, and the mean size of these epitaxial crystallites reaches the 100 nm order. 246,248 Before closing this article, photoemission analyses conducted on these well-defined molecular-molecular heterointerfaces built on the Pn-SC will be summarized in the following paragraphs.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, structural analyses have disclosed well-defined assembly of several organic semiconductor molecules via heteroepitaxial growth on molecular single crystal substrates. [243][244][245][246][247][248][249][250] For instance, it was demonstrated by means of surface X-ray diffraction works that n-type semiconductor molecules of C 60 245 and perfluoropentacene (PFP; C 22 F 14 ) 250 form uniquely oriented crystallites on the single crystal surface of pentacene, and the mean size of these epitaxial crystallites reaches the 100 nm order. 246,248 Before closing this article, photoemission analyses conducted on these well-defined molecular-molecular heterointerfaces built on the Pn-SC will be summarized in the following paragraphs.…”
Section: Resultsmentioning
confidence: 99%
“…PYS is a suitable methodology for electronic characterization of specimens of low electric conductance [24,25], which is the case for intrinsic rubrene as a wide-gap (2.8 eV [26]) semiconductor, and particularly for detecting small modifications at the highest-occupied electronic states in an extreme sensitivity [27][28][29]. GIXD is a technique for determination of the crystal structures of thin films, and has successfully been applied to hetero-epitaxial organic semiconductor junctions built on molecular single crystals for specification of the lattice orientations [30][31][32] and even for evaluation of their crystallographic qualities by using high-resolution apparatuses [33][34][35]. It was confirmed that homoepitaxial rubrene single crystals grow without any apparent lattice distortion up to the thickness of 100 nm by the present GIXD measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, a number of molecular species have been reported to exhibit mobility exceeding that of amorphous silicon in single-crystalline field-effect transistor devices composed of these materials. In the case of optoelectronic devices such as organic photovoltaics, conventional architectures are composed of p-type (donor) and n-type (acceptor) materials of disordered condensates, , and thus making use of the highly efficient charge carrier transport of single-crystalline structures may offer another possible concept to improve the device performance. In this context, epitaxial growth of organic semiconductors is a reasonable approach for obtaining crystalline p–n junctions through self-assembly. In previous studies, highly ordered heteroepitaxial interfaces of uniformly aligned n-type molecular materials formed on single crystals of p-type organic semiconductors have been attained. Moreover, it has been confirmed that single-crystalline thin films with extremely good crystallinity can be obtained by homoepitaxy, where molecules are deposited on single-crystal substrates of the same molecular species. This methodology enables the realization of p–n homojunctions of a monolithic organic semiconductor single crystal by accurately controlled impurity doping .…”
mentioning
confidence: 89%
“…This value is smaller than the overlayer thickness of 50 nm, suggesting that the fmRub overlayer was not single crystalline but included domain boundaries and/or multiple crystallographic phases in the out-of-plane direction. 18 …”
mentioning
confidence: 99%